Elaboración de un: “mejoramiento del servicio de atención a los pacientes de un hospital en el área de consulta externa - Palma Diaz, Gabriela Haidee (2009)
Today, The industries are very changeable and demanding every day, for this reason, the companies that want to continue in competition are obliged to optimize your resources to be able to produce major quantity of product or improve the quality of the service, the Lean methodology help to analyzing the processes tied to the production of products or services classifying and eliminating the type of activities that are not necessary to the process. The use of the Lean tools it is possible to improve the process obtaining economic benefits and marking in the collaborators a style of efficient work. The Improvement of the Service of Attention to the Patients of a Hospital in the area of External Consultation will be based on the analysis of the methodology and tools Read, the implementations and follow-up of the suggested improvements will be at the expense of the same personnel of the company.